Reduced Nitrous Oxide Emissions From Drained Temperate Agricultural Peatland After Coverage With Mineral Soil - Wang, Yuqiao; Paul, Sonja M.; Jocher, Markus; Alewell, Christine; Leifeld, Jens (Frontiers in Environmental Science, 2022)
Peatlands drained for agriculture emit large amounts of nitrous oxide (N2O) and thereby contribute to global warming. In order to counteract soil subsidence and sustain agricultural productivity, mineral soil coverage of drained organic soil is an increasingly used practice. This management option may also influence soil-borne N2O emissions. Understanding the effect of mineral soil coverage on N2O emissions from agricultural peatland is necessary to implement peatland management strategies which sustain agricultural productivity but also reduce N2O emissions. With this study, we aimed to quantify the N2O emissions from an agriculturally managed peatland in Switzerland and to evaluate the effect of mineral soil coverage on these emissions. The study was conducted over two years on a grassland on drained nutrient rich fen in the Swiss Rhine Valley which was divided into two parts, both with identical management. One site was not covered with mineral soil (reference ‘Ref’), and the other site had a ~ 40 cm thick mineral soil cover (coverage ‘Cov’). The grassland was intensively managed, cut 5-6 times per year and received c. 230 kg N ha-1 yr-1 of nitrogen fertilizer. N2O emissions were continuously monitored using an automatic time integrating chamber (ATIC) system. During the experimental period, site Ref released 20.5 ± 2.7 kg N ha-1 yr-1 N2O-N, whereas the N2O emission from Cov was only 2.3 ± 0.4 kg N ha-1 yr-1. Peak N2O emissions were mostly detected following fertilizer application and lasted for 2-3 weeks before returning to the background N2O emssions. At both sites, N2O peaks related to fertilization events contributed more than half of the overall N2O emissions. However, not only the fertilization related N2O peaks, but also background N2O emissions were lower with mineral soil coverage. Our data suggest a strong and continued reduction in N2O emissions with mineral soil cover from the investigated organic soil. Mineral soil coverage, therefore, seems to be a promising N2O mitigation option for intensively used drained organic soils when a sustained use of the drained peatland for intensive agricultural production is foreseen and potential rewetting and restoration of the peatland is not possible.